Filming fast sports movements and problems associated with it - Bilenko A.G.; Govorkov L.P.; Ivanova G.P.; Losin B.E. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to justify the possibilities and problems of using modern light-recording equipment for recording fast sports movements. Methods and structure of the study. Recommendations for the appropriate use of the wide technical capabilities of modern light-recording equipment in solving current pedagogical problems of sports are considered. Results and conclusions. The most difficult to distinguish and poorly eliminated geometric distortions of images of fast sports movements require special control and subsequent correction due to a possible decrease in the quality of assessment of motor actions during the judging process. Such distortions, which are a technical defect in filming, can be assessed by a coach or athlete as an imperfection in motor action. A possible violation of the geometry and shapes of the images negatively affects the work of the coach, who, guided by “distorted” factual information when analyzing the video recording, cannot objectively evaluate either the aesthetics or the sports technique of performing a fast motor action, which interferes with the formation of pedagogical recommendations. A possible sequence of practical actions is shown to obtain high-quality visual information of sporting events using equipment of various classes.